Submission-makers' perceptions of the annual plan process in New Zealand local government : a thesis presented in partial fulfilment of the requirements for a Master of Resource and Environmental Planning at Massey University - Forgie, Vicky Elizabeth (Massey University, 2001)
A purpose of local government in New Zealand as set out in s37k of the amended Local Government Act 1974 was to provide for public participation in local authority affairs. It was intended that this public participation provide citizens with a means of ifluencing local activities, as well as a way of making representatives more accountable to the citizens who elect them. The statutory annual planning and reporting cycle, and the special consultative procedure that it embodies, were the key mechanisms for achieving these objectives. The focus of this research was to determine if the annual planning and reporting cycle which was introduced as an amendment to the Local Government Act 1974 in 1989 provides citizens with an adequate means of participating in local government and provides local authority accountability to citizens. A postal survey of citizens who made submissions in 1999/2000 was undertaken. It covered submission-makers from two city, two district and two regional councils all located in the lower part of the North Island. The overall response rate to the survey was 57.5%. Statistical analysis was used to isolate key interrelationships. The survey responses indicated that most submission-makers value the opportunity the annual plan process provides to have an input into local government affairs. Despite the majority being of the opinion that submissions do not really make a difference or uncertain about whether they did or not, most submission-makers expressed the view they would make another submission in the future. Submissions were generally regarded as of 'some' importance to local authority decision-makers but not 'a lot'. Citizen satisfaction with involvement related more to benefits such as a chance to make their personal views known, than from any concrete outcomes in terms of influence on council decisions or accountability by council. How submission-perceived the public meetings to hear oral submissions and whether or not they were advised of the outcome were closely related to the level of satisfaction from involvement. People making submissions on behalf of organised groups were generally more positive about the process than individual submission-makers.
Keywords: Local government, New Zealand; Political participation; Public opinion; Public participation